2(x+5)=3(x-10)

Simple and best practice solution for 2(x+5)=3(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)=3(x-10) equation:


Simplifying
2(x + 5) = 3(x + -10)

Reorder the terms:
2(5 + x) = 3(x + -10)
(5 * 2 + x * 2) = 3(x + -10)
(10 + 2x) = 3(x + -10)

Reorder the terms:
10 + 2x = 3(-10 + x)
10 + 2x = (-10 * 3 + x * 3)
10 + 2x = (-30 + 3x)

Solving
10 + 2x = -30 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
10 + 2x + -3x = -30 + 3x + -3x

Combine like terms: 2x + -3x = -1x
10 + -1x = -30 + 3x + -3x

Combine like terms: 3x + -3x = 0
10 + -1x = -30 + 0
10 + -1x = -30

Add '-10' to each side of the equation.
10 + -10 + -1x = -30 + -10

Combine like terms: 10 + -10 = 0
0 + -1x = -30 + -10
-1x = -30 + -10

Combine like terms: -30 + -10 = -40
-1x = -40

Divide each side by '-1'.
x = 40

Simplifying
x = 40

See similar equations:

| 22-5x=-28 | | 3x^2+2x-30=0 | | (-5)(10)= | | y+-4=-15 | | 3X^2+10X=-2 | | 9= | | 4a*9a= | | 96=2(6+2x)+2(x) | | (-12)+(-23)= | | (x^2+13)=225 | | 10=x+8 | | 32-12t+t^2= | | 21x^2+11x-6=0 | | 2*(x+5)=37 | | 3x-2=x+8 | | 14x=-17 | | x-7+x=3x+4 | | 1-2x+4x=8 | | 2(0)+5y=0 | | x+(-14)=5 | | y-7xy=3y+4 | | 11+4x=7x-13 | | 2x+5(0)=0 | | 6x+123=16x-7 | | 3b-5=16 | | (2-3x)*5-4(8-x)=0 | | 15x^2-91x+6= | | -5x+3(0)=6 | | 8-8x=34-22x | | -35-8x=10x+19 | | 19764845-7564524+5424-214241=11991504 | | 3+3y=3-(5y+2) |

Equations solver categories